The Emerging Roles of Nanocarrier Drug Delivery System in Treatment of Intervertebral Disc Degeneration-Current Knowledge, Hot Spots, Challenges and Future Perspectives - Hu Y; Yang R; Liu S; Song Z; Wang H (Dove Medical Press, 2024)
Yunxiang Hu,1,2,* Rui Yang,1,2,* Sanmao Liu,1,2,* Zefeng Song,3 Hong Wang1,2 1Department of Orthopedics, Central Hospital of Dalian University of Technology, Dalian City, Liaoning Province, People's Republic of China; 2School of Graduates, Dalian Medical University, Dalian City, Liaoning Province, People's Republic of China; 3School of Graduates, Dalian University of Technology, Dalian City, Liaoning Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Hong WangDepartment of Orthopedics, Central Hospital of Dalian University of Technology, No. 826, Southwestern Road, Shahekou District, Dalian City, Liaoning Province, People's Republic of China, Email wanghong@dmu.edu.cnAbstract: Low back pain (LBP) is a common condition that has substantial consequences on individuals and society, both socially and economically. The primary contributor to LBP is often identified as intervertebral disc degeneration (IVDD), which worsens and leads to significant spinal problems. The conventional treatment approach for IVDD involves physiotherapy, drug therapy for pain management, and, in severe cases, surgery. However, none of these treatments address the underlying cause of the condition, meaning that they cannot fundamentally reverse IVDD or restore the mechanical function of the spine. Nanotechnology and regenerative medicine have made significant advancements in the field of healthcare, particularly in the area of nanodrug delivery systems (NDDSs). These approaches have demonstrated significant potential in enhancing the efficacy of IVDD treatments by providing benefits such as high biocompatibility, biodegradability, precise drug delivery to targeted areas, prolonged drug release, and improved therapeutic results. The advancements in different NDDSs designed for delivering various genes, cells, proteins and therapeutic drugs have opened up new opportunities for effectively addressing IVDD. This comprehensive review provides a consolidated overview of the recent advancements in the use of NDDSs for the treatment of IVDD. It emphasizes the potential of these systems in overcoming the challenges associated with this condition. Meanwhile, the insights and ideas presented in this review aim to contribute to the advancement of precise IVDD treatment using NDDSs.Keywords: lumbar disc herniation, intervertebral disc degeneration, nanocarrier drug delivery system, targeted therapy, regenerative medicine